2020
DOI: 10.3390/nu12082373
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Challenges with the Categorization of Foods Processed at Home: A Pilot Methodology to Inform Consumer-Facing Guidance

Abstract: The objective of this study was to inform consumer-facing dietary guidance by (1) adapting the current University of North Carolina at Chapel Hill (UNC) food processing framework to include a home processing (HP) component and (2) pilot testing the adapted version using a nationally representative sample of foods consumed in the U.S. The UNC framework was adapted to include guidelines for categorizing home-prepared (HP) foods. The original UNC and adapted HP frameworks were used to code dietary recalls from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…There is no consensus regarding which dishes should be disaggregated into their ingredients before categorising them by processing levels ( 30 , 32 ) . For instance, the classification system used in the European Prospective Investigation into Cancer and Nutrition (EPIC) study breaks down all recipes ( 20 ) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is no consensus regarding which dishes should be disaggregated into their ingredients before categorising them by processing levels ( 30 , 32 ) . For instance, the classification system used in the European Prospective Investigation into Cancer and Nutrition (EPIC) study breaks down all recipes ( 20 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies disaggregated dishes prepared away from home, such as restaurant meals ( 8 , 9 ) , whereas others did not disaggregate ( 15 ) , excluded ( 23 ) or did not mention how to treat them. A previous study has also highlighted inconsistencies in classification methods and indicated that the misclassification of foods may contribute to the misrepresentation of the consumption, nutrient profile and associated health outcomes of HPF ( 32 ) . In this study, the energy contribution of HPF was higher when dishes prepared away from home were classified without recipe disaggregation (48·3 %) than when they were disaggregated (32·9 %), whereas both estimates were strongly correlated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zero-calorie foods (e.g., water) were not classified and excluded from the analyses. Since the reporting of recipes was not required in ASA24, home-made mixed dishes were classified as "un-disaggregated home-made dish" under the unprocessed or processed foods categories, depending on the processing level of the core ingredients (35). Energy intake from foods was quantified and reported in either absolute (kcal/day) and/or relative values (% kcal/day).…”
Section: Classification Of Foods By the Degree Of Processingmentioning
confidence: 99%